Foreign Tax Credit Limitations and Preferred Stock Issuances - Collins, Julie H.; Shackelford, Douglas A. (Journal of Accounting Research, 1992)
Preferred Stocks, Foreign Tax Credits, Tax Reform Act, Tax burden